PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA MENGGUNAKAN PENDEKATAN KONSTRUKTIVISME - Fiska, Lenni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Through this research, the writer applies Konstruktivisme approaching in processes learning for there are many student. Observational stage is describe to plot, implement, and step-up study results. Type of this research is observational action braze, with use qualitative approaching and quantitative one consisting of two cycles. Observational student of class four and observational. Analisis’s result to learning planning on. Cycle is 74,99% experience step-ups on the second cycle, by derived 92,85%. Result observinging to activity learns in learning on I, cycle is 70,31% experience step-ups on the second cycle 95,31%. Result observinging to student activity in learning on I cycle is 70,31% experience step-ups on the second cycle, by derived 90,62%. Learned result before perform research average 65,45 on the second cycle, average 85,38. In short, the research action class uses konstruktivisme could increase the student’s study result for exact science course. Kata Kunci: hasil belajar,IPA, pendekatan, pembelajaran, dan pendekatan konstruktivisme